Disability: Caregivers’ perceptions of disabled children and youth - Carolina Giaconi Moris; Teletón Chile; Zoia Pedrero Sanhueza; Teletón Chile; Pamela San Martín Peñailillo; Teletón Chile (Escuela de Psicología, Pontificia Universidad Católica de Valparaíso, 2017)
Disability is a socio-cultural and historical construction that exists to personal, family and social level. This condition affects people with disabilities and their caregivers. This study aimed to describe caregivers' perceptions about disability. For this, a qualitative research was conducted through six focus groups and qualitative content analysis. Three main categories emerged: the meaning of disability; difficulties related to disability and; approaches to solve the difficulties. The caregiver's perception about disability is associated to social and bio psychosocial models, perceiving mainly as a situation of difference. They identified difficulties associated with disability in the areas of family, society, accessibility, transport, health, and education system, similar to those reported by the international literature. Participants proposed a number of approaches to improving difficulties, including the visibility of disability, an active role from disabled people and their caregivers, and State responsibility.